2014
DOI: 10.1055/s-0034-1385844
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ear Fullness, Earache, and Temporomandibular Joint Disorders in the Elderly

Abstract: Introduction An earache (otalgia or ear pain) is pain in one or both ears that may last a short or long time. Earache is prevalent in the population with temporomandibular joint disorders (TMJDs), but there is a dearth of epidemiologic studies regarding the association between TMJD and ear pain and ear fullness in older people. Objective To assess the presence of earache and ear fullness in elderly patients with TMJD. Methods A cross-sectional study was conducted in independently living, elderly individuals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…Temporomandibular disorders (TMD) is a collective term referring to musculoskeletal disorders affecting the temporomandibular joints (TMJ) and the muscles of mastication . Several studies have shown that TMD is associated with otologic symptoms such as tinnitus, otalgia, and vertigo, suggesting the possibility of TMJ pathologies as a contributor to EF . EF was reported to be manifested in approximately 75% of TMD patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporomandibular disorders (TMD) is a collective term referring to musculoskeletal disorders affecting the temporomandibular joints (TMJ) and the muscles of mastication . Several studies have shown that TMD is associated with otologic symptoms such as tinnitus, otalgia, and vertigo, suggesting the possibility of TMJ pathologies as a contributor to EF . EF was reported to be manifested in approximately 75% of TMD patients .…”
Section: Introductionmentioning
confidence: 99%
“…7 Several studies have shown that TMD is associated with otologic symptoms such as tinnitus, otalgia, and vertigo, suggesting the possibility of TMJ pathologies as a contributor to EF. [8][9][10] EF was reported to be manifested in approximately 75% of TMD patients. 11 It has been suggested that EF associated with TMD is the result of stomatognathic dysfunction, which transmits unnecessary charges to the middle ear muscles or bony network between the TMJ and middle ear.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, en la literatura se reconoce una alta frecuencia de otalgia refleja y tinnitus en pacientes con DTM 1,27,28 , al respecto Macedo y cols. encontraron una asociación significativa entre la presencia de DTM y otalgia (odds ratio = 2,3) en pacientes adultos mayores 29 . Molina y cols.…”
Section: Epidemiologíaunclassified
“…La otalgia es un motivo de consulta frecuente, correspondiendo al 4% de las consultas en medicina general 9 . En los niños, la otalgia primaria es la más común 7,9 , pero en los adultos la secundaria es más frecuente, alcanzando en algunas series sobre un 50% de las causas 5,6,10,11 . Si analizamos la otalgia por género en adultos, la otalgia primaria es más frecuente en hombres y la otalgia secundaria es más frecuente en mujeres 7,12 , siendo también más frecuente en este género la patología temporomandibular y las neuralgias 6,7 .…”
Section: Epidemiologíaunclassified
“…12 , esto llega a un 62,8% de los casos. Sin embargo, esta afirmación histórica se basa en evidencia controversial y poco sólida 10 , la cual además hay que contextualizarla en la realidad de la población estudiada, la cual en algunos casos no es extrapolable a nuestra población. La mayoría de los estudios recientes determinan que la patología cervical es la causa más frecuente de OR, seguido por la afección de la articulación temporomandibular (ATM) y en tercer lugar la patología dental 1,4 .…”
Section: Epidemiologíaunclassified